A Review on Cooperative Diversity Techniques Bypassing Channel Estimation - Hushairi, Zen; Al-Khalid, Hj Othman; Ong, Sylvia Ai Ling; Mahmood, Adnan; Bello, Olalekan (SENRA Academic Publishers, 2016)
Wireless communication technology has seen a remarkably fast evolution due to its capability to provide a quality, reliable and high-speed data transmission amongst the users. However, transmission of information in wireless channels is primarily impaired by deleterious multipath fading, which affects the quality and reliability of the system. In order to overcome the detrimental effects of fading, Multiple-Input Multiple-Output (MIMO) technology is an attractive scheme that employs multiple transceiver antennas to carry the data over the same frequency band over a variety of signal paths. This technology has shown great solutions due to its ability to provide better spectral efficiency, capacity, throughput and robustness of the data transmission. But in practice, it is impractical to install multiple antennas on small-sized devices. Hence, to overcome the limitations of MIMO gain in the future wireless networks, cooperative diversity has recently draw in attention due to its ability to circumvent the difficulties of implementing actual antenna arrays in Multiple-Input and Multiple-Output (MIMO). By exploiting the broadcast feature of the wireless medium, cooperation among multiple nearby nodes is formed for data transmission. At the receiver, the signals are either coherently or differentially detected. Coherent detection requires exact channel estimation, which is difficult to apply in a time-varying channel. Hence, when the nodes are mobile, or when the channel is inaccurately estimated, the differential detection techniques that omit channel estimation become an alternative as compared to coherent detection. This article presents a review of the differential transmission techniques for cooperative diversity networks. The article begins with the development of the differential detection techniques. Then, the concept of double-differential technique with the presence of carrier offset is addressed. The review of these studies is presented so as to provide directions for future developments.